Experiencias didácticas enfocadas a un proyecto de monitoreo de laboratorios con internet de las cosas (IoT). - Quintero, Juan Humberto Vela; Hernandez, Martha Isaberl Aguilera; Hernández, Israel Uribe; Vázquez, Victor Manuel Pérez; Martinez, Jean Carlo Garibay (Revista Daena: International Journal of Good Conscience)
The article focuses on the impact of project-based teaching experiences in university laboratories using the emerging technology of the Internet of Things (IoT). Through a qualitative methodology, it concludes that the integration of IoT in higher education promotes active, meaningful, and collaborative learning, facilitating the rapid understanding of technological concepts and the development of professional skills in programming, data analysis, and problem-solving. Furthermore, the use of IoT in educational settings allows for efficient resource management and real-time decision-making, establishing itself as an innovative pedagogical strategy that links academia with the needs of the productive sector. Finally, it is recommended to increase investment in emerging technologies to enhance these teaching experiences and to deepen future research on their educational impact.